Mathematical Spatial Ability Reviewed from Students’ Self-Confidence in the PBL Model with Teacher and Peer feedbacks Assisted by Geogebra - Puspitasari, Elsa; Kartono, Kartono; Junaedi, Iwan (Unnes Journal of Mathematics Education Research, 2021)
This research aims to describe mathematics spatial skill reviewed from the self-confidence of students in high, moderate, and low categories. This research was conducted in the eighth grade JHS Hasannudin 6 Semarang, in the academic year 2018/2019. This mixed-method research used a sequential explanatory strategy. It is a procedure to collect quantitative and qualitative data orderly. The technique of collecting quantitative data was done by mathematics-spatial skill test. Meanwhile, the qualitative data was done by documentation, questionnaire, and interview. The findings showed mathematics-spatial skill of each-category student’s self-confidence had various mastery indicators. The students with high-self-confidence tended to be more consistent in mastering spatial visualization, spatial relation, and mental rotation. The spatial-orientation and spatial-perception aspects of high self-confidence students were sometimes successful and sometimes not successful. The moderate-self-confidence students tended to master spatial visualization, spatial relation, and spatial orientation aspects. However, there were several subjects with moderate-self confidence in the five aspects. Subjects with low-self-confidence tended to be more consistent in mastering spatial visualization and spatial perception. There were subjects with low-self-confidence who only mastered four aspects of mathematics-spatial skills.